Influence of cooling rate on microstructure development of AlSi9MgMn alloy - Stanić D.; Zovko-Brodarac Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Aluminum alloys are widely applied in automotive, aircraft, food, and building industries. Multicomponent technical AlSi9MgMn alloy is primarily intended for high cooling rate technology. Controlled addition of alloying elements such as iron and manganese as well as magnesium can improve mechanical and technological properties of the final casting depending on the cooling conditions during solidification. The aim of this investigation is the characterization of AlSi9MgMn alloy microstructure and mechanical properties at lower cooling rates than those for which this alloy was primarily developed. Thermodynamic calculation and thermal analyses revealed solidification sequence in correlation to the microstructure investigation as follows: development of primary dendrite network, precipitation of high temperature Al15(Mn,Fe)3Si2 and Al5FeSi phases, main eutectic reaction, precipitation of intermetallic Al8Mg3FeSi6 phase, and Mg2Si as a final solidifying phase. Influence of microstructure features investigation and cooling rate reveals significant Al15(Mn,Fe)3Si2 morphology change from Chinese script morphology at low, irregular broken Chinese script morphology at medium, and globular morphology at high cooling rate. High manganese content in AlSi9MgMn alloy together with high cooling rate enables the increase of Fe+Mn total amount in the intermetallic Al15(Mn,Fe)3Si2 phase and encourage favourable morphology development, all resulting in enhanced mechanical properties in as-cast state.